Boosting Photocatalytic Hydrogen Production via Interfacial Engineering on 2D Ultrathin Z‐Scheme ZnIn2S4/g‐C3N4 Heterojunction. (16th December 2021) - Tan, Mengxi; Ma, Yuan; Yu, Chengye; Luan, Qingjie; Li, Junjie; Liu, Chuanbao; Dong, Wenjun; Su, Yanjing; Qiao, Lijie; Gao, Lei; Lu, Qipeng; Bai, Yang
Abstract: 2D layered nanomaterials as photocatalysts have attracted much attention in the field of solar hydrogen production due to their unique electronic structure and abundant active sites. Nevertheless, the rational design and interfacial regulation of 2D Z‐scheme heterojunction are still challenging. Herein, an ultrathin 2D ZnIn2 S4 /g‐C3 N4 Z‐scheme heterojunction is precisely constructed via in‐situ growth of ZnIn2 S4 on the g‐C3 N4 . By carefully regulating the interface structure in heterojunction, the hydrogen evolution performance can be greatly improved. The optimized photocatalyst exhibits a remarkable photocatalytic activity without Pt as cocatalyst, which is primarily ascribed to the synergistic effect of abundant active sites, enhanced photoresponse, and valid interfacial charge transfer channels. Meanwhile, the spectroscopic analyses and density functional theory (DFT) calculation results comprehensively prove that the promoted interfacial charge separation in 2D Z‐scheme heterojunction is another key factor for the enhanced photocatalytic performance. This work offers a new avenue for the rational design of ultrathin Z‐scheme heterojunction photocatalysts with improved photocatalytic performance through interfacial engineering. Abstract : A 2D ultrathin Z‐scheme ZnIn2 S4 /g‐C3 N4 heterojunction is precisely constructed by using a ligand‐assisted hydrothermal method. The optimized sample exhibits excellent photocatalytic H2 evolution performance (14.799 mmol g −1 h −1 ) without Pt as a cocatalyst. The experimental characterizations and DFT calculations comprehensively demonstrate the roles of morphology control, interfacial regulation, and especially the Z‐scheme mechanism in improving the photocatalytic performance.